2020
DOI: 10.31577/sp.2020.01.789
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Differences in Cognitive Style, Individualism/Collectivism and Map Reading between Central European and East Asian University Students

Abstract: The article examines cross-cultural differences encountered in the cognitive processing of specific cartographic stimuli. W e conducted a comparative experimental study on 98 participants from two different cultures, the first group comprising Czechs (N = 53) and the second group comprising Chinese (N = 22) and Taiwanese (N = 23). The findings suggested that the Central European participants were less collectivistic, used similar cognitive style and categorized multivariate point symbols on a map more analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
5
19
0
Order By: Relevance
“…According to research, there are consistent cultural differences in how individuals regard themselves and their relationships, which may have an impact on whether or not they use social support to cope with stress. Westerners see people as autonomous and apart from others, but Asians see people as intrinsically related to others (56)(57)(58). Because Asians place a premium on connection with their social group, this distinction may lead to the idea that coping through social support is more widespread among them.…”
Section: Cultural Contextmentioning
confidence: 99%
“…According to research, there are consistent cultural differences in how individuals regard themselves and their relationships, which may have an impact on whether or not they use social support to cope with stress. Westerners see people as autonomous and apart from others, but Asians see people as intrinsically related to others (56)(57)(58). Because Asians place a premium on connection with their social group, this distinction may lead to the idea that coping through social support is more widespread among them.…”
Section: Cultural Contextmentioning
confidence: 99%
“…Dumetz and Gáboriková (2017) study confirmed that the Czech Republic is more individualistic than Slovakia, but others found the exact opposite result ( Bašnáková et al, 2016 ). Furthermore, the Czech Republic seems to be less individualistic than the Netherlands ( Bašnáková et al, 2016 ) and less collectivistic and, similarly, individualistic as East Asians ( Lacko et al, 2020 ). Another study found that Czechs are not only more individualistic, but simultaneously also more collectivistic than Czech Vietnamese ( Čeněk, 2015 ).…”
Section: Individualism and Collectivism In The Czech Republicmentioning
confidence: 99%
“…Conversely, as the results of the study [6] suggest, a population with a higher level of map literacy may prefer the intrinsic method in certain tasks. Another potentially significant change which affects how we work with maps is the type of formal education or the cultural background of users [71][72][73].…”
Section: Discussionmentioning
confidence: 99%